KNOWLEDGE SHARING IN SOCIAL MEDIA: AN ANALYSIS OF DEIXIS ON AN INDONESIAN PODCAST PROGRAM - Hanindya Sekar Ayu A; Ahmad Bukhori Muslim (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2023)
Podcasting has become a common phenomenon among Indonesian youth which can draw pragmatic attention. This study investigates the types of deixis used in Raditya Dika’s podcast and analyzes factors that influence its uses. The data of this qualitative research were verbal communication in some selected episodes of podcast programs. Furthermore, the data were analyzed by Levinson’s (1983) about deixis use and Holmes’ (2013) about factor. Analysis found four types of deixis; person, time, discourse, and place. The most dominant used was person deixis with 644 occurrences (86%) to show knowledge-sharing. The findings indicate that the use of different deixis was due to some factors such as social distance or solidarity, status or power, formality, and function.